Personal satellite services : 5th International ICST Conference, PSATS 2013, Toulouse, France, June 27-28, 2013, Revised Selected Papers - Beylot, André-Luc; Montpetit, Marie-Jose; Lucani, Daniel; Mucchi, Lorenzo; Dhaou, Riadh (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International ICST Conference on Personal Satellite Services, PSATS 2013, held in Toulouse, France, in June 2013. The 18 revised full papers presented were carefully reviewed and selected from numerous submissions. They are grouped in the following topical sections: satellite for emergency and aerocommunication, satellite for networking, resource management, and air interface.